2016
DOI: 10.1590/s1806-92902016000700009
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and microbiological parameters of frozen and chilled chicken meat

Abstract: -With this study we aimed to evaluate and compare physicochemical and microbiological characteristics of frozen and chilled chicken meat. Only the prime cuts (breast, thighs, and drumsticks) were considered for the analysis of chemical composition, pH, color, water-holding capacity (WHC), thawing-cooking loss (TCL), and shear force (SF). For microbiological analysis, mesophilic bacteria, thermotolerant coliforms, and Salmonella spp. were considered. The frozen and chilled chicken meat showed no PSE (pale, soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 11 publications
4
10
1
1
Order By: Relevance
“…However, as a reflection of a competitive exclusion, the emergence and reemergence of new serotypes may explain the reason the occurrence of Salmonella sp. still remains high in the poultry chain (Ribeiro et al, 2007;Rall et al, 2009;Yamatogi et al, 2012;Fernandes et al, 2016), corroborating with the high occurrence observed in this work.…”
Section: Resultssupporting
confidence: 92%
“…However, as a reflection of a competitive exclusion, the emergence and reemergence of new serotypes may explain the reason the occurrence of Salmonella sp. still remains high in the poultry chain (Ribeiro et al, 2007;Rall et al, 2009;Yamatogi et al, 2012;Fernandes et al, 2016), corroborating with the high occurrence observed in this work.…”
Section: Resultssupporting
confidence: 92%
“…In organic poultry production, restrictions on the use of antibiotics and antiparasitic drugs, and outdoor breeding of the animals play a role in increasing the microbial risks of organic poultry meat (Thamsborg 2001, Engvall 2001, Mead 2004b. The TMAB, TPAB, E. coli, coliform, Pseudomonas spp., mold and yeast counts in the present study were different (lower or higher results) from the results of the studies carried out with conventional frozen chicken meats depending on the type of microorganism (Eglezos et al 2008, Patsias et al 2008, Atlan and İşleyici 2012, Santosh et al 2014, Fernandes et al 2016. Thus, it is difficult to ascertain that the TMAB, TPAB, E. coli, coliform, Pseudomonas spp., mold and yeast counts in organic chicken meat analyzed in this study were higher than those reported in conventional chicken meat.…”
Section: Discussioncontrasting
confidence: 81%
“…Total ash content was determined after the complete mineralization of 5 g of the meat sample at 550-650°C in a muffle Carbolite oven type AAF1100, Hope Valley, UK. To assess the post-heat treatment leakage, 30 g of meat samples were weighed, placed, and kneaded in 150 cm 3 beakers and weighed (accuracy of 0.01 g). e samples, thus prepared, were covered with polyethylene foil and heated in a water bath at 72 ± 2°C for 30 minutes and subsequently cooled [17].…”
Section: Quality Assessment Of Breast Meatmentioning
confidence: 99%
“…A speci c feature of meat is its short shelf life [3]. A signi cant part of the poultry meat in commercial circulation is o ered as chilled meat.…”
Section: Introductionmentioning
confidence: 99%